Effect of probiotic (Bacillus subtilis) in Macrobrachium rosenbergii culture - Mohd Azmi, Farah Diyana (2012)
A study on the effect of Bacillus subtilis on Macrobrachium rosenbergii culture was conducted on July 2012 until October 2012 at Wet Laboratory, Block A, Faculty of Agriculture, Universiti Putra Malaysia (UPM), Serdang, Selangor. The aim of this study was to determine the effectiveness of probiotic, Bacillus subtilis on growth performance of Macrobrachium rosenbergii post larvae. The post larvae of M. rosenbergii with an initial size range between 1.2 to 1.5 cm per post larva and stocking density of 25 post larva per aquaria was used. The experiment was carried out with three different treatments which consisted of T1 (control), T2 (commercial pellet feed-107 CFU Bacillus subtilis) and T3 (commercial pellet feed-1010 CFU Bacillus subtilis). Each treatment was replicated four times and was conducted in recirculation system in glass aquaria for 12 weeks. The data was analyzed using One-Way ANOVA by SPSS (Statistical Package for Social Science) software. The result of growth performance and survival from this experiment showed that M. rosenbergii post larvae treated with diet T3 significantly different (p<0.05) compared to other treatments.